W damskiej gotowalni. Zwyczaje higieniczne kobiet w XIX wieku na przykładach ze zbiorów Muzeum Warmii i Mazur w Olsztynie - Malinowska, Anna (W zwierciadle rzeczy, 2022)
The subject matter of this article is an attempt to show the issues related to health and hygiene of women in the 19th century. Its most important aspect is the concept of a boudoir as a private chamber and a kind of sanctuary, in which all activities were carried out in order to maintain hygiene and beautiful appearance. The furnishings of a boudoirs and how they differed depending on the social position and the wealth of the owner will be extensively described, based on the example of exhibits from the Museum of Warmia and Masuria and guidebook literature. By showing objects of everyday use that served the purpose of maintaining hygiene and aesthetic appearance, the article illustrates the process of transformation that took place in women’s hygiene habits in the 19th century.